From the New Testament Isagogics - Кели, Џон (Sabornost - The Theological Year-book, 2012)
The well-know British patristic scholar John Norman Davidson Kelly, in his book Early Christian Doctrines (5th ed., Adam & Charles Black, London 1980), that is a standard secondary writing and a seminary textbook in Oxford, exposes in six sections some crucial scriptural matters, such as reception of the Old Testament by the early Christian community, with a special stress on the way how the early Church Teachers and later Church Fathers used to quote from it in their writings, and not only from the protocanonical books but also from the deutorocanonical books that have been accepted both in the Orthodox and the Roman-Catholic Churches as well. The scholar explains the process of collecting New Testament books into a canon being of the same sacral authority as the Old Testament books, always quoting Church Fathers as best witnesses of canonicity of each writing that was accepted by the universal mind of the Church. He also deals with the inspiration of the Holy Scriptures in general, giving a special stress on the unity of the Two Testaments. While exposing various schools of exegesis in the first four centuries of Christianity, Dr. Kelly deals in details with the typology in the Old Testament books, giving some examples of how Church Fathers interpreted them as well as some Jesus’ parables, and in relation to this the way how the two Christian schools of interpretation, those of Alexandria and that of Antioch, used to approach and explain such significant matters. Thereby, the author is always aware of the complexity of this subject matter due to some heretic, Montanistic, Marcionite or Gnostic teachings on what preconditions of a canonical book should be.